Doing Business Economy Profile 2016 : Rwanda - World Bank Group (World Bank, Washington, DC, 2015)
This economy profile for Doing Business 2016 presents the 11 Doing Business indicators for Rwanda. To allow for useful comparison, the profile also provides data for other selected economies (comparator economies) for each indicator. Doing Business 2016 is the 13th edition in a series of annual reports measuring the regulations that enhance business activity and those that constrain it. Economies are ranked on their ease of doing business; for 2015 Rwanda ranks 62. A high ease of doing business ranking means the regulatory environment is more conducive to the starting and operation of a local firm. Doing Business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 189 economies from Afghanistan to Zimbabwe and over time. Doing Business sheds light on how easy or difficult it is for a local entrepreneur to open and run a small to medium-size business when complying with relevant regulations. It measures and tracks changes in regulations affecting 11 areas in the life cycle of a business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, resolving insolvency and labor market regulation. The data in this report are current as of June 1, 2015 (except for the paying taxes indicators, which cover the period from January to December 2014).